Development of a statistically reliable pseudorandom bit sequence - Mandrona, Maria; Maksymovych, Volodymyr; Kostiv, Yuriy; Harasymchuk, Oleh (Lviv Polytechnic Publishing House, 2015)
A statistically reliable pseudorandom bit sequence generator has been developed on the basis of additive lagged Fibonacci generator. Studies have been conducted into its the quality of its operation according to the criteria of systemic theoretical approach to the design of generators. The said criteria include: pulse repetition period, statistical characteristics, linear complexity, key information amount (length of key) and rate of response.
Keywords: pseudorandom generator; protection of information; pseudorandom numbers; ensuring block of statistical security; statistic characteristics